Mars North Pole Edifices Profiles - Marina Sanchez-Bayton; Erwan Tréguier; Miguel Herraiz; Patrick Martin; Akos Kereszturi; Beatriz Sanchez-Cano (2019)
This data set contains geophysics derived data from the MOLA altimeter on board Mars Global Surveyor mission. It contains morphometric information, as well as topographic profiles from 201 edifices (positive topographic elevations) analysed from the North Polar region of Mars. Specifically, from the Scandia Cavi and Olympia Undae regions. This data set accompanies the following paper: Sánchez-Bayton, M., Tréguier, E., Herraiz, M., Martin, P., Kereszturi, A., and Sánchez-Cano, B., (2019), New Landforms in Scandia Cavi and Olympia Undae, North Polar Region of Mars. Discrimination of possible volcanoes edifices. Journal of Geophysical Research Planets, 124, (awaiting for DOI). Abstract: A survey of edifices on Olympia Undae sand sea and Scandia Cavi in the northern circumpolar region of Mars has been performed using images from Mars Express, Mars Global Surveyor, and Mars Reconnaissance Orbiter. These are key areas for the evolution of the Northern Polar cap as they can cast light on the gypsum formation process that occur in there, which is essential for liquid water. This study has led to identifying 201 elevated edifices, more than 90% of them not classified before, with diameters between 6 and 86 km. Considering their morphometric parameters and image-based appearances, these positive topographic features have been classified into five categories: cratered cones, impact craters, and simple, irregular, and peaked domes. Cratered cones and impact craters include all crater shaped edifices and are far more numerous than the dome-shaped ones. 100 of 130 crater-shaped edifices are probably not impact craters, although can be erroneously taken as eroded remnants of earlier craters of this type. Regarding their origin, different types of formation processes are evaluated. There is not a unique definite origin as they could be explained by various causes, such as impact craters, mud domes, pingos and volcanic activity, although the main cause seems to be either hydrothermal or volcanic nature. The formation mechanism ...